Aquaponic Monitoring System - Mok , Jian Qin; Bin Mardi, Noor Azizi (Evolution in Electrical and Electronic Engineering, 2020)
Aquaponics has always been hot topics in food sustainability and agriculture. To maintain an aquaponics system, attention is needed on the water condition of the system. With city expanding and human population increasing, there is less and less space available for agriculture and aquaculture to operate [10]. Aquaponics might be one of the solutions for the crisis but aquaponics requirement much more effort in maintaining than the traditional soil-based agriculture. In this project, a monitoring system for aquaponics is designed, enable user to remotely monitor the condition of aquaponics. The system comes with emergency alert function that can prevent the further loss on the aquaponics when problem occurs. Moreover, the data of the condition of the water in the aquaponics system are recorded for user to better identify the cause and solution for problems that occurs.